Modulation of the Bifidobacterial Communities of the Dog Microbiota by Zeolite - Sabbioni, Alberto; Ferrario, Chiara; Milani, Christian; Mancabelli, Leonardo; Riccardi, Enzo; Di Ianni, Francesco; Beretti, Valentino; Superchi, Paola; Ossiprandi, Maria C. (Frontiers in Microbiology, 2016)
During last decades canine health and well being is becoming an important issue for human owners. In dogs, several factors including diet, pathogenic bacterial and stress conditions can affect the composition of the gut microbiota. In this study, we evaluated the effect of dietary chabazitic zeolitite (CZ) supplementation on the contribution of bifidobacteria to the faecal microbiota in training hunting dogs. Faecal microbiota cataloguing based on 16S rRNA microbial profiling analyses highlighted an increase of Lactobacillus and Bifidobacterium in animals treated with CZ, with a simultaneous decrease of pathogens associated with dog gastrointestinal infections, such as Klebsiella and Enterobacter. A detailed profiling of the bifidobacterial population of dogs receiving CZ based on the ITS-based sequencing approach, revealed an enhancement bifidobacterial of species typical of animals such as Bifidobacterium animalis and Bifidobacterium pseudolongum. Moreover, these analyses identified the occurrence of putative new bifidobacterial taxa in both treated and untreated samples.